Country economic status is strongly associated with burn survival - validation of the (modified) ABSI - Julia Elrod; Christoph Mohr; Ludvik Branski; Joshua M. Peterson; Fionna M. Wood; Dale W. Edgar; Pius Agbenorku; Shobha Chamania; Anant Sharma; Flavio N. Novaes; Jean Bosco Katabogama; Michael Boettcher; et al. (International Journal for Equity in Health)
Abstract Background Predicting burn-related mortality is vital for family counseling, triage, and resource allocation. Several of the burn-specific mortality prediction scores have been developed, including the Abbreviated Burn Severity Index (ABSI) in 1982. However, these scores are not tested for accuracy to support contemporary estimates of the global burden of burn injury. This study compares burn mortality across countries with varying economic levels, as indicated by the Human Development Index (HDI), to assess if a modified ABSI (mABSI) offers enhanced predictive accuracy. Methods A retrospective study was performed, including over 90,000 patients from seven sources in five continents, including two burn registries and five referral burn centers. Data from 2015 to 2019 were collected, including age, gender, presence of inhalation injury, full-thickness burn, percentage of total body surface area, and outcome. The participating countries were classified based on the HDI and mortality was predicted using both the original and the modified ABSI. Results After removal of incomplete data, 74,460 sets remained for the analysis. Significant variations in population demographics, sample sizes, total body surface area (TBSA), and age distributions across the studied regions were noted. The modified ABSI demonstrated a smaller deviation from the 95% CI of the true survival probability than the original ABSI in countries with a very high or high HDI, indicating improved accuracy here. In these countries, the original ABSI overestimates mortality. Conversely, in countries with a middle or low HDI, the original ABSI remains more accurate, reflecting the significantly greater burn related mortality in countries with a low HDI. Conclusion In burn patients, the probability of survival remains highly dependent on the level of development of a country. Our results support the use of the modified ABSI in countries with a (very) high HDI, yet in resource constraint settings, the original ABSI seems to provide more accurate predictions. These findings underscore the need for adaptive models that take into account socioeconomic variables, potentially guiding health policy adjustments and emphasizing the necessity of resource allocation and training in lower HDI countries. Such adaptations could enhance clinical outcomes and reduce disparities in burn care effectiveness globally.